#TITLE_ALTERNATIVE# - ARROISI (NIM: 15011072), ABDURRAHMAN
Economic growth lead to an increase in traffic volume on a road section. One way that can be done to avoid congestion and road damage that can happen is to widen the road and increase the structural capacity. Road widening and pavement structural improvement is expected to improve service road on Jalan Batas Kota Medan – Batas Kota Lubuk Pakam, North Sumatra. Road widening and structural enhancement of road comprises structural widening of the road, a review of the existing road geometry, road overlay thickness design, the new design of rigid pavement, as well as the design of the new road drainage system. The design of the widening of the road includes the calculation of the V/C ratio and determination of the required road width. A review of road geometry includes the review of horizontal alignment and vertical alignments that take aspects of ease, safety, and economical into consideration. Overlay thickness design involves determining the thick overlay for each segment. The new rigid pavement design includes determining the type of rigid pavement and concrete slab thickness, together with the dimensions of reinforcement of the connection. The design of drainage system aims to determine the dimension of street gutters, culverts, and storm drains. The results are as follows. There will be widening of the road by 0.5 meters in each direction. Road geometry need not change. Thickness of added pavement obtained is in the range of 7 to 30 centimeters for along the way. Thickness of rigid pavement for road widening obtained is 34 cm for the Lubuk Pakam direction and 35 cm for the Medan direction. The drainage channel is a rectangle-shaped concrete with dimensions of 0.5 meters × 0.9 meters and is only used on the road above the ground (at grade).